Imperialism and the entrepreneurial state - Dark, K.; Gulamhussen, M. A. (Entrepreneurship: theory, networks, history, 2010)
Although there have been many studies of individual empires (for example, Cain and Hopkins, 1993), the theory of imperialism has changed little since the surveys by Fieldhouse (1967) and others. Most more recent theoretical work takes a cultural history perspective (for example, Hardt and Negri, 2000). Economic research has tended to focus on the benefits generated by trade and investment flows and the costs of imperial defence (for example, O’Brien, 1988); the resultant cost–benefit evaluations shed light on decolonization and other specific issues. However, the basic questions of why, when and where empires develop, how far they spread and how long they last have received little systematic attention. This chapter considers the contribution that the economic theory of institutions can make to the analysis of these larger questions (see, for example, Buckley and Casson, 1976; Williamson, 1985; North, 1990). It identifies six key insights that can be applied to imperialism: 1. Some states are more entrepreneurial than others because they provide strong incentives for individual discovery and innovation (for example, promoting freedom of travel, association and expression). 2. Newly-discovered knowledge is a global public good; it is therefore efficient to apply it simultaneously in all territories to which it is relevant (for example, applying the same mining technology in several different mineral-rich countries). 3. States have a role in supplying local public goods (for example, law and order, transport and communications infrastructure, and certain types of health and education); they can also establish property rights and regulations under which...